Peran Moderasi Product Innovation pada Pengaruh Online Marketing dan Market Orientation terhadap Marketing Performance Bisnis Restoran (Bistro) di Kota Makassar - Rahmat, Rahmat; Abdullah, Wahidah (Study of Scientific and Behavioral Management, 2024)
Business has an important role in the economic sustainability of society in Indonesia, especially in Makassar City. With business, it is hoped that it will be able to make the economic cycle better. The aim of this research is to determine the influence of online marketing on the marketing performance of restaurant (bistro) businesses in Makassar City, to determine the influence of market orientation on the marketing performance of restaurant (bistro) businesses in Makassar City, to determine the influence of Product Innovation Moderating Online Marketing on Marketing Performance restaurant (bistro) business in Makassar City and to determine the influence of Product Innovation in moderating Market Orientation on Marketing Performance of restaurant (bistro) businesses in Makassar City. This research is a type of associative research using a quantitative approach with a sample of 120 respondents. The sample in this research uses the Hair formula with the research location being the restaurant business in Makassar City. The method for calculating the sample size is technical purposive sampling for restaurant businesses in Makassar City with certain criteria. Data processing is assisted by using SmartPLS software. The results of this research show that online marketing has a positive and significant effect on marketing performance, market orientation has a positive and significant effect on marketing performance, product innovation moderates online marketing on marketing performance, product innovation moderates market orientation on marketing performance. Keywords: Online Marketing, Market Orientation, Marketing Performance, Product Innovation